Assessment of the Impact of Methadone Assisted Treatment (Mat) On Combating Drug Addiction in Tanzania (International Journal of Scientific Research and Management (IJSRM), 2025)
This study examine the extent to which Methadone-Assisted Treatment (MAT) is used to redress drug addiction at Mwananyamala Referral Hospital in Tanzania. A mixed-methods design was employed, with 260 participants recruited from the MAT Clinic at the hospital. The result show that while there are efforts to increase availability of MAT Clinics, many clients still face barriers in accessing services. The study highlights the importance of outreach programs and community-based initiatives in identifying and referring clients to MAT services. Furthermore, the findings suggest that clients who have relapsed or defaulted from treatment face significant challenges in accessing services, highlight the need for targeted intervention to support individuals struggling with addiction.